Physical fitness of Latin America children and adolescents: a protocol for a systematic review and meta-analysis. Issue 5 (3rd May 2021) - Godoy-Cumillaf, Andrés; Bizzozero-Peroni, Bruno; Tomkinson, Grant R; Brazo-Sayavera, Javier
Abstract : Introduction: Physical fitness (PF) is an important indicator of health in children and adolescents. Internationally, test batteries have been used to assess overall PF. In Latin America, however, while PF has been widely measured, there is no accepted test battery, making it difficult to monitor and/or compare the PF levels of Latin children. The aim of this study, therefore, is to systematically review and potentially meta-analyse the peer-reviewed literature regarding the assessment of PF in Latin American children and adolescents. Methods and analysis: This systematic review and meta-analysis will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols statement. The systematic literature search will be performed in MEDLINE, Scopus, SciELO, EMBASE, Cochrane Library, Web of Science, SPORTDiscus, LILACS and Latindex (Spanish) to locate articles published up to April 2021. Eligible studies will include both descriptive and analytic study designs. Meta-analyses are planned for sufficiently homogeneous PF outcomes with regard to statistical and methodological characteristics. Narrative syntheses are planned for PF outcomes that are considered to be too heterogeneous. The statistical program STATA V.15 will be used for meta-analyses, with subgroup analyses performed according to the characteristics of included studies. Ethics and dissemination: This systematic review and meta-analysis protocol is designed to provide updated evidence on the PF of Latin American children and adolescents. Findings from this review may be useful for teachers, researchers and other professionals responsible for paediatric fitness and health promotion/surveillance. The results will be disseminated through peer-reviewed scientific publications, conferences, educational talks and infographics. PROSPERO registration number: CRD42020189892.